2008
DOI: 10.2976/1.2976662
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion and response to synthetic nanopatterned environments by steering receptor clustering and spatial location

Abstract: (2008) Cell adhesion and response to synthetic nanopatterned environments by steering receptor clustering and spatial location, HFSP Journal, 2:5, 276-285,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 85 publications
3
93
0
2
Order By: Relevance
“…Basement membranes are not the same in all tissues but differ in the geometry of 5-200 nm size pits, pores, protrusions, and fibers so that nanostructured biomaterials can mimic the spatial organization and separation distances which are characteristic of each specific basement membrane. 42 In the present study, rough and porous surfaces in which pillars and grooves are separated by a distance ,58 nm, which corresponds to the maximum distance required for correct establishment of focal adhesions, 25,43 were obtained from silicon and compared not only to flat silicon but also to plastic surfaces which are routinely utilized for traditional 2D cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Basement membranes are not the same in all tissues but differ in the geometry of 5-200 nm size pits, pores, protrusions, and fibers so that nanostructured biomaterials can mimic the spatial organization and separation distances which are characteristic of each specific basement membrane. 42 In the present study, rough and porous surfaces in which pillars and grooves are separated by a distance ,58 nm, which corresponds to the maximum distance required for correct establishment of focal adhesions, 25,43 were obtained from silicon and compared not only to flat silicon but also to plastic surfaces which are routinely utilized for traditional 2D cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The mean speed decreases with time for all surfaces, most likely due to the decrease in the cell-free gap area. The ability of cells to migrate is a response that is coupled to cell adhesion, [65] where stronger cell adhesion coincides with a less migratory behavior displayed by the cells. Vinculin is necessary for binding cell surface integrin receptors to the ECM www.advancedsciencenews.com www.advhealthmat.de adhesion molecules, which in part controls the process of cell spreading and movement.…”
Section: Cell Migrationmentioning
confidence: 99%
“…[62][63][64] The feature sizes described in these studies are in the range of 80-300 nm and higher, which is over a density threshold corresponding to a spacing of integrin-adhesive RGD ligands per unit area, which is ≈70 nm. [13,65] Some common effects of ordered nanotopographies with feature sizes exceeding 70 nm on cells include (1) reduced area of adhesion complexes, (2) increased filopodia, (3) biased orientation, and (4) constant traction forces. By contrast, increased adhesion has been reported on random nanoposts.…”
Section: Cell Adhesionmentioning
confidence: 99%
“…Their results showed that cell activities, such as cell spreading, stress ber formation, and focal contacts were maximized on nanodot arrays with spacing of 28 and 58 nm, but were decreased on arrays with spacing of 73 and 85 nm. 8,41,42) These results indicated that cell adhesion sites should be located in optimal arrangements for enhancement of cell activities. Cell interactions with extracellular surfaces are mediated by clustering of integrins into focal adhesion complexes and activation of intracellular signaling cascades to the nucleus and cytoskeleton.…”
Section: Cell Morphologymentioning
confidence: 96%